An Ecological Approach to Understanding Program Management Practices for Food Pantries in Rural Communities - Kenya M. Cistrunk; Brittney Oliver; Laura Jean Kerr; Maria Trinh; Caroline Kobia; Leslie Hossfeld; Kecia R. Johnson; Claudette Jones (The University of Alabama, 2022)
This qualitative study was conducted in Mississippi, a state comprised of 82 counties, many of which are rural and highly impoverished. To gain a greater understanding of the food needs of residents from across the state, a representative sample of food pantries from each region of the state was identified. For this project, researchers with the Mississippi Food Insecurity Project formed a partnership with the Mississippi Food Network to interview partner pantries across the state. Interviews were conducted with food pantry managers and volunteers to examine various issues, challenges, and successes related to their operations. All interviews were transcribed and coded using a systematic analysis of codes to generate major themes related to pantry management protocols. Using an ecological framework, our study yielded five major areas of consideration for optimal pantry management: volunteer recruitment, operating and control systems, patron needs, collaboration, and advocacy.